Preamplification with dUTP and Cod UNG Enables Elimination of Contaminating Amplicons - Andersson, Daniel; Svec, David; Pedersen, Cathrine; Henriksen, Jørn Remi; Ståhlberg, Anders (International journal of molecular sciences, 2018)
Analyzing rare DNA and RNA molecules in limited sample sizes, such as liquid biopsies and single cells, often requires preamplification, which makes downstream analyses particularly sensitive to polymerase chain reaction (PCR) generated contamination. Herein, we assessed the feasibility of performing Cod uracil-DNA N-glycosylase (Cod UNG) treatment in combination with targeted preamplification, using deoxyuridine triphosphate (dUTP) to eliminate carry-over DNA. Cod UNG can be completely and irreversibly heat inactivated, a prerequisite in preamplification methods, where any loss of amplicons is detrimental to subsequent quantification. Using 96 target assays and quantitative real-time PCR, we show that replacement of deoxythymidine triphosphate (dTTP) with dUTP in the preamplification reaction mix results in comparable dynamic range, reproducibility, and sensitivity. Moreover, Cod UNG essentially removes all uracil-containing template of most assays, regardless of initial concentration, without affecting downstream analyses. Finally, we demonstrate that the use of Cod UNG and dUTP in targeted preamplification can easily be included in the workflow for single-cell gene expression profiling. In summary, Cod UNG treatment in combination with targeted preamplification using dUTP provides a simple and efficient solution to eliminate carry-over contamination and the generation of false positives and inaccurate quantification.
Keywords: uracil; Animals; Reproducibility of Results; Uracil-DNA Glycosidase; kontaminace DNA; Gadus morhua; analýza jednotlivých buněk; Deoxyuracil Nucleotides; reprodukovatelnost výsledků; DNA Contamination; zvířata; Single-Cell Analysis; uracil-DNA-glykosidasa; Gene Expression Profiling; Uracil; deoxyuracilnukleotidy; stanovení celkové genové exprese